Functional roles for noise in genetic circuits - Eldar, Avigdor; Elowitz, Michael B. (Nature (London), 2010)
Noise in gene circuits Even genetically identical cells in a homogeneous environment can behave quite differently from one another because of the prevalence of unavoidable random fluctuations, or 'noise', in their levels and activities. Noise is something of a nuisance when it comes to developing reliable genetic circuits, and various control circuits have evolved to cope with it. But a new wave of studies is showing that noise can, and does, provide vital functions that would be difficult or impossible to achieve in 'noiseless' gene circuits. In this Review, Avigdor Eldar and Michael Elowitz discuss the emerging principles that connect noise, the architecture of gene circuits in which it appears, and the biological functions that it enables. The genetic circuits that regulate cellular functions are subject to stochastic fluctuations, or ‘noise’, in the levels of their components. Noise, far from just a nuisance, has begun to be appreciated for its essential role in key cellular activities. Noise functions in both microbial and eukaryotic cells, in multicellular development, and in evolution. It enables coordination of gene expression across large regulons, as well as probabilistic differentiation strategies that function across cell populations. At the longest timescales, noise may facilitate evolutionary transitions. Here we review examples and emerging principles that connect noise, the architecture of the gene circuits in which it is present, and the biological functions it enables. We further indicate some of the important challenges and opportunities going forward.